Students’ Perception of Self-Confidence in Speaking English as a Foreign Language in the Classroom - Indah Sari; Doni Efrizah; Nabilah Yolanda (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study aimed to explore students' perceptions of self-confidence in speaking English as a foreign language within classroom settings. Utilizing qualitative methods, data were collected through administration of questionnaires to 5th semester students of Technology and Information System Study Program at Institut Teknology Sawit Indonesia (ITSI) Medan intake 2025-2026. Then, the study applied Miles, Huberman and Saldana’s steps (2014) in analysing the data. The results showed that most students had positive and good perception of self-confidence in speaking English in the classroom. Moreover, it revealed that self-confidence significantly influences students' willingness to engage in spoken communication. Factors contributing to self-confidence include supportive classroom environments, peer interactions, and effective teaching strategies. Furthermore, the study highlights the importance of fostering a positive atmosphere that encourages risk-taking in language use, ultimately enhancing students' speaking abilities. Implications for educators include the need to implement practices that build self-confidence and promote active participation in language learning. Keywords: perception, self-confidence, speaking, English